Model Pendidikan Politik: Studi Kasus PKS DPD Sleman, Yogyakarta - Nasiwan Nasiwan (Jurnal Cakrawala Pendidikan, 2005)
AbstractThis article is based on a research study conducted to achieve some understanding of the model of political education employed by the regionalbranch of the political party called Partai Keadilan Sejahtera in the Sleman Regency, Yogyakarta. The central theme of the study was what model of political education was employed by the party to produce members possessing simultaneously adequate loyalty to the party as well as an active participants political awareness and culture.The study was conducted by using as its main method a study of the literature complemented with in-depth interviews with those consideredknowledgeable of the information required for the interest of the sudy. The data obtained were then analyzed by means of a method of critical analysis.The results of the study indicate that, first, in anticipation of the 2004 general elections, the regional branch of the party has conducted politial education for its members as well as the public, second, that branch has employed a model of political education specific in terms of learning objectives, structure of learning materials, management of the teaching-learning process, and learning participants, and, third, the model of political education employed can be developed for appropriate employment by other political parties.Key words: political education, Partai Keadilan Sejahtera, general elections